Pengaruh Kualitas Pelayanan Perpajakan Terhadap Kepatuhan Wajib Pajak - Hadi, Nor; Mahmudah, Umi (IAIN Kudus, 2018)
This article explains the results of empirical research on the effect of service quality represented by tangible, reliability, responsiveness, assurance, and empathy variables in encouraging taxpayer behavior to comply with tax obligations. In line with the rules of quality service theory, the dimensions of quality service are satisfaction explanations which are triggers for taxpayer compliance. The research was conducted at the Tax Service Office, and the respondents were taxpayers, both individual and corporate taxpayers. The number of respondents is 89 people out of 100 people who were targeted for research. Sampling using the random sampling method. Data were analyzed using multiple linear regression. The results show that three variables do not significantly affect taxpayer compliance in carrying out tax obligations, namely tangible, reliability and assurance. This is because there are still contingency factors that are considered and conditioned included in the model. These contingency factors are in the form of both the contextuality that is on the side of the tax employee, as well as the background, motives and special conditions of the taxpayer. Meanwhile, two variables show significant, there are reliability and empathy.